"Writing biochips": high-resolution droplet-to-droplet manufacturing of analytical platforms. Issue 7 (11th March 2022) - Arrabito, Giuseppe; Gulli, Daniele; Alfano, Caterina; Pignataro, Bruno
Abstract : Depletion-free molecular ink deposition with accurate volume control allows for the fabrication of droplet-based bioanalytical assays. Abstract : The development of high-resolution molecular printing allows the engineering of analytical platforms enabling applications at the interface between chemistry and biology, i.e. in biosensing, electronics, single-cell biology, and point-of-care diagnostics. Their successful implementation stems from the combination of large area printing at resolutions from sub-100 nm up to macroscale, whilst controlling the composition and volume of the ink, and reconfiguring the deposition features in due course. Similar to handwriting pens, the engineering of continuous writing systems tackles the issue of the tedious ink replenishment between different printing steps. To this aim, this review article provides an unprecedented analysis of the latest continuous printing methods for bioanalytical chemistry, focusing on ink deposition systems based on specific sets of technologies that have been developed to this aim, namely nanofountain probes, microcantilever spotting, capillary-based polymer pens and continuous 3D printing. Each approach will be discussed revealing the most important applications in the fields of biosensors, lab-on-chips and diagnostics.